Inhibition of Fibroblast Activation in Uterine Leiomyoma by Components of Rhizoma Curcumae and Rhizoma Sparganii - Feng, Yewen; Zhao, Yumin; Li, Yao; Peng, Teng; Kuang, Yu; Shi, Xingming; Wang, Gang; Peng, Fu; Yu, Chenghao (Frontiers in Public Health, 2021)
Background: The herbs Rhizoma Curcumae and Rhizoma Sparganii (RCRS) are often used in traditional Chinese medicine for the treatment of uterine leiomyoma (UL). The effectiveness of RCRS for the treatment of UL has been confirmed in our previous studies. Purpose: This study aimed to investigate the molecular mechanism by which RCRS inhibits the activation of fibroblast activation protein (FAP) and prevents UL in rats. Study Design and Methods: A Sprague Dawley (SD) rat model of UL was established via estrogen and progesterone load combined with external stimulation. Histological analyses, enzyme-linked immunosorbent assays, and western blotting were performed to evaluate the effect of RCRS on UL and elucidate its mechanism of action. Results: Our data showed that the treatment of SD rats with RCRS significantly reduced the expression of extracellular matrix component collagen, FAP, and transforming growth factor beta (a FAP-activating factor) and the phosphorylation of the cell proliferation pathway-related signaling factors AKT/MEK/ERK. Conclusion: Our results suggest that RCRS is effective in the prevention and treatment of UL in rats, and RCRS may exert its functions by inhibiting the activation of tumor-associated fibroblasts and cell proliferation and by improving the tumor extracellular matrix.